Comparison of Time-Varying and Landmark Analysis Methods in Estimating the Association Between Medication Adherence and Outcomes: A Heart Failure Cohort - Hsu, Benjumin; Jorm, Louisa (International Journal of Population Data Science, 2020)
Introduction Cardiovascular disease (CVD) is a leading contributor to disease burden worldwide. Older people hospitalized with CVD might experience significant decline in physical function and loss of independence. Objectives and Approach The aim of this study was to investigate the use of community aged care (CAC) and permanent residential aged care (PRAC) services 3 months, 6 months and 12 months after hospital admission for myocardial infarction (MI), stroke and congestive heart failure (CHF). Survey data from the 45 and Up Study (2006-09) for 266,942 people aged 45+ was linked with records for hospital stays (APDC), aged care service use (NACDC), and deaths (RBDM) for 2006-14 through CHeReL and AIHW. Relative risks of using aged care (CAC or PRAC) after MI, stroke or CHF hospitalization were estimated using Cox regression. We described and visualized sequences of health service states (none, re-hospitalization, CAC, PRAC, death) after the index hospitalization. Results Compared with people without MI, people hospitalized with a principal diagnosis of MI (multivariable-adjusted HR:1.11, 95%CI:1.04-1.18), stroke (HR:1.52, 95%CI:1.43-1.61) and CHF (HR:1.12, 95%CI:1.06-1.19) were more likely to use CAC within 3 months of the hospital discharge. Likewise, people with MI (HR:1.16, 95%CI:1.03-1.29), stroke (HR:2.81, 95%CI:2.58-3.05) and CHF (HR:1.36, 95CI:1.24-1.49) were more likely to enter PRAC within 3 months of discharge. Similar findings were observed for 6 months and 12 months. MI, stroke and CHF patients were more likely to die but less likely to be re-hospitalized after the first 3 months. The number use of CAC and PRAC remains unchanged over 12 months. While this study provides a broadly representative sample of the older population, participants may be healthier than the general population. Conclusion / Implications CVD increases use of community and residential care services. Coordination of cardiac and stroke rehabilitation is warranted to maximize ageing in place.